2014
DOI: 10.3906/bot-1309-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arbuscular mycorrhizal inoculations and cotyledon removal on early seedling growth of Pongamia pinnata

Abstract: Pongamia pinnata (L.) Pierre, a fast-growing oil-seed-producing tree legume, has the ability to grow on wastelands. It can be utilized for biofuel plantation on such lands. The preconditioning of young seedlings during the early stage of development with efficient arbuscular mycorrhizal fungi (AMF) confers several benefits enhancing the possibility of their establishment in fields after outplanting from nurseries. However, before recommending these fungi for inoculation, the suitable AMF species must be identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Manjunath et al, 1989;Awotoye et al, 1992;Osundina 1995;Guissou et al, 1998;Schneider et al, 2013;Verma et al, 2015). (Shukla et al, 2010;Jha et al, 2014Jha et al, , 2015. This could explain the reason that why tested AMF species did not work synergistically with each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manjunath et al, 1989;Awotoye et al, 1992;Osundina 1995;Guissou et al, 1998;Schneider et al, 2013;Verma et al, 2015). (Shukla et al, 2010;Jha et al, 2014Jha et al, , 2015. This could explain the reason that why tested AMF species did not work synergistically with each other.…”
Section: Resultsmentioning
confidence: 99%
“…Mycorrhizal symbiosis can be found in nearly all types of ecological situations and most plant species are able to form this symbiosis naturally (Jaizme-Vega et al, 2006;. These associations occur naturally in the fields, favoring plant development by increasing nutrient uptake, growth rates and hormonal activities (Shukla et al, 2010;Hashmi et al, 2010;Jha et al, 2012Jha et al, , 2014Jha et al, , 2015. The positive effects of mycorrhizae on seedlings survival and growth under nursery conditions are well documented (Smith et al, 2009;Guissou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Chugh, (2019) found that seedlings of plants i.e., P.cineraira, D. sissoo, E. tereticornis, A. indica and A. excelsa grown in pots inoculated with mycorrhizae fungi performed significantly better that uninoculated soils. Jha et al, (2014) in Pongamia pinnata. Shukla et al, (2013) in Dalbergia sissoo.…”
Section: Resultsmentioning
confidence: 99%
“…This creates a good opportunity to explore the use of AMF in enhancing cocoa seedling establishment in West Africa. The plethora of research that suggest that preconditioning of young seedlings with efficient arbuscular mycorrhizal fungi (AMF) makes plants stronger and helps in their establishment in fields (Cekic et al, 2012;Jha et al, 2014;Navarro Garcia et al, 2011;Shi et al, 2012) reiterate our hypothesis that the concept could be applied to tree crops like cocoa seedlings in the wake of drought stress caused by climate change. This innovation could result in superior and stronger growth of cocoa seedling and improve their establishment on farmers' fields, with the potential to reflect in higher cocoa yield and improved living conditions of the majority of people that depend on the cocoa sector.…”
Section: Role Of Amf In Plants Under Water Stress (Drought) Conditionmentioning
confidence: 99%